2015
DOI: 10.1590/2359-3997000000040
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia in young patients with type 1 diabetes mellitus

Abstract: Objective: The association between type 1 diabetes mellitus (T1D) and dyslipidemia (DLP) increases the risk of cardiovascular disease (CVD). The aim of this study was to evaluate the presence of dyslipidemia in young T1D patients. Materials and methods: The study design was cross-sectional and descriptive. We reviewed medical records of T1D patients followed at an endocrinology service, from 1998-2012. Data collected: gender, actual age and age at diagnosis, duration of T1D since diagnosis, body mass index (BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
48
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 26 publications
11
48
1
2
Order By: Relevance
“…In our cohort, 23% of all patients were dyslipidaemic, and this is consistent with dyslipidaemia rates of 22–29% in children with diabetes found in Germany . Much higher rates of 72.5% were found in a cohort of adolescents and young adults in Brazil . Dietary intervention for dyslipidaemia includes improving glycaemic control, weight reduction (if indicated) and decreasing saturated fat intake as recommended by the American Diabetes Association .…”
Section: Discussionsupporting
confidence: 88%
“…In our cohort, 23% of all patients were dyslipidaemic, and this is consistent with dyslipidaemia rates of 22–29% in children with diabetes found in Germany . Much higher rates of 72.5% were found in a cohort of adolescents and young adults in Brazil . Dietary intervention for dyslipidaemia includes improving glycaemic control, weight reduction (if indicated) and decreasing saturated fat intake as recommended by the American Diabetes Association .…”
Section: Discussionsupporting
confidence: 88%
“…also found that dyslipidemia was more common in adolescents than younger children (15), what would be expected based on previous studies (17,18). Females were particularly affected.…”
supporting
confidence: 72%
“…In another paper featured in this issue of Archives of Endocrinology and Metabolism, Homma and cols. found that 15.1% of children with T1D are overweight or obese (15), which is lower than previously reported nationwide in the BrazDiab (16). They also verified that dyslipidemia is common in this population, reaching 72.5% of their study group.…”
supporting
confidence: 51%
“…8 The prevalence of DLP in the general population, including children, has recently increased. 9 DLP in DM patients is likely to play an important role in the development of atherogenesis.…”
Section: Data Collection and Analysismentioning
confidence: 99%